CORRELATION OF OPERATIVE FINDINGS WITH PRE-OPERATIVE CLINICAL SIGNS AND ANALYSIS OF X-RAYS IN PATIENTS WITH AIRWAY FOREIGN BODIES - Asif, Muhammad; Haroon, Tahir; Qureshi, Waqar -ur-Rehman; Jamil, Muhammad; Malik, Sohail; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2010)
Background: Foreign body aspiration is one of the commonly encountered emergencies in ENT and still it remains a significant cause of mortality and morbidity. However with the development of modern endoscopic techniques and controlled anaesthesia, most foreign bodies can be removed safely with a bronchoscope. Methods: This study was carried out at Department of ENT, Head and Neck Surgery, Ayub Medical College, Abbottabad from 1st Jan 2003 to 30th June 2005. Total 81 patients were registered in the study. Two patients, in whom the foreign body could not be removed, were excluded from the study. Results: The most consistent finding was decreased air entry on chest auscultation on the side of impacted foreign body which was present in 72 (91.1%) patients. The second most consistent finding was audible wheeze on the side of impacted foreign body found in 42 (53.2%) patients. The most common finding on Chest X-ray was emphysema found in 19 (61.3%) patient, followed by atelactasis in 9 (28%) patients while 3 (9.7%) patients had normal Chest x-ray. Conclusion: The pre-operative clinical signs in patient with aspirated foreign body give an idea about the site of foreign body in an airway. Although chest x-ray gives an idea about the pathological changes in respiratory tract it has little impact in the management of a patient with aspirated foreign body. Keywords: Airway, foreign body, chest x-ray